Real-time Acquisition of the Distributed Data by using an Intelligent System N. C. Gaitan - Gaitan, N. C. (Elektronika ir Elektrotechnika, 2010)
For real time applications, the specific time requirements represent the main constraints, and their controlling is an essential factor in order to establish the quality of the accomplished services. The time constraints might be found within more application areas, such as the automatization of industrial equipments, the embedded systems, the control of vehicles, monitoring the nuclear devices, supervising the scientific experiments, robotics, conditioning of audio and video multimedia data flows, monitoring the surgical interventions, as well as supervising the stock exchange operations. Within this paper, the hardware and software architecture of an intelligent system for real time acquisitions of the distributed data is presented. This intelligent system is represented by means of an embedded device, performed with a STR710FZ2 microcontroller and a RTX real time kernel.